The recall of single paired associates with an A-B, A-Br sequential paradigm - Campos, Leonel; Siojo, Luis (1969)
A sequential A-B, A-Br paradigm was adopted in a short-term memory task to test the possibility that novel combinations of the same stimulus and response items would result in proactive interference (PI) in the recall of paired associates. No definite evidence on increasing PI was found, thus supporting the notion of a "limited capacity" hypothesis as an explanation for short-term memory behavior.
Includes bibliographical references (page 42).